(3QSGdI GdJbQjHs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ef Gddg JHGQc hJYGdi deG Ndb GdMjhGf eNJdaI GdCeRLI hGdWHGFY de jLYd CZPjJge ef LfS hGMO s
(3BNQgG (B:s
(3hEf ELJeY TF dg bO jNQLg aUO hGdbi hGdESgGd ai gPg GdaUhd hjOhe fbGA GdHOf hjMUd GdCef ef GdeYGhOI Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdQSGI GdKGdK hGdKdGKhfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs